2021
DOI: 10.2196/23737
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Newborn Clinical Decision Support Software (NoviGuide) in a Rural District Hospital in Eastern Uganda: Feasibility and Acceptability Study

Abstract: Background Lack of trained health care workers and nonadherence to national guidelines are key barriers to achieving high-quality newborn care in health care facilities in low- and middle-income countries. Traditional didactic approaches addressing these barriers fail to account for high staff turnover rates and result in temporary behavior change. NoviGuide, a clinical decision support software designed to standardize neonatal care through point-of-care assessments, has the potential to align beds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Mobile CDSSs have been successfully used to improve hypertension control in India, and have been developed for neonatal care in Ghana, Kenya, and Uganda. [34][35][36][37][38][39] In Bangladesh, electronic CDSSs have also been shown to improve WHO diarrhea guideline adherence including reducing non-indicated antibiotic use by 28.5% in children under five. 15 While prior studies of CDSS targeting antibiotic use have focused on improving adherence to guidelines, our prediction tool provides the clinician with an estimation of viral diarrhea etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile CDSSs have been successfully used to improve hypertension control in India, and have been developed for neonatal care in Ghana, Kenya, and Uganda. [34][35][36][37][38][39] In Bangladesh, electronic CDSSs have also been shown to improve WHO diarrhea guideline adherence including reducing non-indicated antibiotic use by 28.5% in children under five. 15 While prior studies of CDSS targeting antibiotic use have focused on improving adherence to guidelines, our prediction tool provides the clinician with an estimation of viral diarrhea etiology.…”
Section: Discussionmentioning
confidence: 99%
“…While a lack of research persists regarding CDSSs in LMICs, their use has risen recently due to the increasingly ubiquitous use of smartphones globally. Mobile CDSSs have been successfully used to improve hypertension control in India, and have been developed for neonatal care in Ghana, Kenya, and Uganda Watson et al, 2019 ; Anchala et al, 2015 ; Muhindo et al, 2021 ; Bucher et al, 2021 ; Amoakoh et al, 2017 ; Bilal et al, 2018 . In Bangladesh, electronic CDSSs have also been shown to improve WHO diarrhea guideline adherence including reducing non-indicated antibiotic use by 28.5% in children under five Khan et al, 2020 .…”
Section: Discussionmentioning
confidence: 99%
“…Mobile CDSSs have been successfully used to improve hypertension control in India, and have been developed for neonatal care in Ghana, Kenya, and Uganda. [32][33][34][35][36][37] In Bangladesh, electronic CDSSs have also been shown to improve WHO diarrhea guideline adherence including reducing non-indicated antibiotic use by 28.5% in children under five. 14 While prior studies of CDSS targeting antibiotic use have focused on improving adherence to guidelines, our prediction tool provides the clinician with an estimation of etiology.…”
Section: Discussionmentioning
confidence: 99%
“…This compares favourably with other digital systems, for example, a national review of UK Emergency Department Electronic Health Records reported a median SUS of 53 47 and is similar to a digital clinical decision support tool piloted in Uganda, mean SUS 93.5, n = 12. 21 In 2018 Neotree-beta was implemented in Sally Mugabe Central Hospital in Zimbabwe (annual delivery rate ~12 000) as a Quality Improvement tool for neonatal sepsis. 42 Discharge data capture and laboratory data capture functions were added.…”
Section: Data Capture and Interfacementioning
confidence: 99%